Monitoring the Effectiveness of Master’s Programs Implementation - V. P. Ignatiev; L. F. Varlamova (Высшее образование в России)
The paper highlights a mechanism for monitoring the effectiveness of master’s programs implementation. The authors dwell on the experience of M.K. Ammosov North-Eastern Federal University in the developing of such a mechanism. Five main blocks are considered as the monitoring criteria reflecting the effectiveness of educational programs implementation, such as: 1) demand, 2) resource provision, 3) quality control, 4) contingent of students, and 5) employment of educational program graduates. Each criterion contains three main indicators for which points are calculated. On the results obtained from the monitoring carried out using this methodology, the master programs are ranked according to their efficiency, taking into account the total number of points scored on all the criteria units. After analyzing the data obtained, it turns out which block or direction of work has lag in the implementation of educational program and administrative measures are taken to remedy the situation. The outcome of this monitoring should be the improvement of the quality and efficiency of master’s programs implementation at federal university.